(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Providing the body with oxygen is one of the most pressing problems of modern physiology and theoretical medicine, since hypoxia underlies the pathogenesis of most diseases, and an in-depth study of these processes is of great practical importance. For the normal functioning of the mechanisms for maintaining the body’s energy balance, it is necessary to preserve the parameters that characterize the functional abilities of oxygen transport systems. Disruption of this process leads to disruption of oxygen homeostasis and the occurrence of hypoxia, i.e. to a discrepancy between O2 delivery and the metabolic demand of an organ or cell. The main universal indicator of oxygen homeostasis, reflecting the adequacy of oxygen delivery and consumption, is the oxygen tension in the blood (PaO2). During hypoxia, PO2 changes either due to a decrease in barometric pressure (hypobaric hypoxia -HH), or due to a decrease in the O2 fraction in the inspired air under normal atmospheric pressure conditions (760 mmHg) (normobaric hypoxia -NН). It has been established that in both hypobaric and normobaric hypoxia, the observed changes in functional indicators are a consequence of a decrease in the partial pressure of oxygen in the environment (PO2).